(untitled) (Fiep Bulletin - online, 2012)
This paper aims to understand and identify issues regarding cultural identity in postmodernity, resorting to literature reviews, which reflects conceptual discussions about the subject, education, science, culture and man’s relationship in postmodern society as from the paradigm crisis settled in the end of the 20th century and the beginning of the 21st century.